1981
DOI: 10.1002/ar.1092000314
|View full text |Cite
|
Sign up to set email alerts
|

Aqueductal tanycytes in the rabbit brain: A Golgi study

Abstract: Utilizing Golgi-Cox impregnation, tanycytes were found in the ependyma of the cerebral aqueduct of the neonatal and adult rabbit. These tanycyte somas showed a variety of shapes, apical projections into the aqueduct, and basal processes (shafts) projecting into the mesencephalon, particularly into the periaqueductal gray (PAG). The shafts showed a variety of branching patterns, and sometimes abutted or terminated on capillaries or on specific neuronal elements. Other shafts coiled within the PAG or terminated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
1
1

Year Published

1983
1983
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 41 publications
0
8
1
1
Order By: Relevance
“…With regard to the tanycyte, Tennyson and Pappas (1962) claimed that these cells were only transitional and not present in the adult. This does not agree with the results presented here as abundant numbers of tanycytes were found in the cerebral aqueduct of the adult rabbit, nor does it agree with observations made by Burnett and Felten (1981) in a Golgi study of the adult rabbit cerebral aqueduct.…”
Section: Ependymacontrasting
confidence: 99%
See 1 more Smart Citation
“…With regard to the tanycyte, Tennyson and Pappas (1962) claimed that these cells were only transitional and not present in the adult. This does not agree with the results presented here as abundant numbers of tanycytes were found in the cerebral aqueduct of the adult rabbit, nor does it agree with observations made by Burnett and Felten (1981) in a Golgi study of the adult rabbit cerebral aqueduct.…”
Section: Ependymacontrasting
confidence: 99%
“…A t the present time, there are no reports on the structure of the cerebral aqueduct in any species using scanning electron microscopy. Apart from early descriptions of the ultrastructure of the normal aqueductal ependyma using the transmission electron microscope by Tennyson and Pappas (1962) in the foetal and adult rabbit and by Brightman and Palay (1963) in the adult rat, along with Golgi investigations of the aqueductal tanycyte in the rabbit (Burnett and Felten, 1981), there have been no other attempts to provide an examination of the cerebral aqueduct in any species by light microscopy or by scanning or transmission electron microscopy. The present report is the first to comprehensively examine the ultrastructure of the cerebral aqueduct of the rabbit using scanning and transmission electron microscopy and Golgi impregnation methods.…”
mentioning
confidence: 99%
“…In the brainstem of P8 cats, the R2D5-positive palisade embraced most neurons ofthe raphe nuclei, and even in adult cat, a large number of neurons in the dorsal parts of the raphe neuronal system were located within the palisade of the R2D5-positive processes. In Golgi studies of developing and adult rabbit brainstem, Felten and coworkers (12)(13)(14) found that raphe nuclei neurons frequently abutted radial processes oftanycytes (which presumably correspond to R2D5-positive radial processes) lining the floor of the fourth ventricle, and suggested that these tanycytes constitute a communication channel between the cerebrospinal fluid of the fourth ventricle and medullary raphe neurons. However, with the Golgi method, which randomly labels a small number of cells, it is difficult to examine the spatial arrangement of the entire midline radial glial system.…”
Section: Discussionmentioning
confidence: 99%
“…This process does not finish for some time after birth, because the persistence of certain foetal signs may also be observed in 2-month-old lambs (perhaps older individuals). It is probably one of the causes of shape variability not only in prenatal but also postnatal ependymal cells, which has led some authors to attempt their typing (Milhouse 1971;Burnett and Felten 1981;Fernández-Llebrez et al 1981;Rajtová 1987).…”
Section: Discussionmentioning
confidence: 99%